Theorising gendered childhoods and girls' schooling: Poverty, patriarchy and girls' education in urban India. (May 2021) - Yunus, Reva
This paper offers gendered accounts of girls' schooling and childhood from urban India. It challenges global 'girl effect' narratives by grappling with the interplay of poverty and caste patriarchy and how it shapes families' struggles and concerns and girls' (re)productive labour, (un)freedoms and classroom experiences. Moving beyond the notion of 'multiple childhoods' it develops a conceptual framework that accounts for the way the state, the market, economic inequalities and local patriarchies inscribe poor girls' schooling and work. Drawing upon ethnographic work with Class VIII students in a state school it also unpacks girls' negotiation of classed and casted patriarchies.